Neutrophil/lymphocyte ratio elevation in renal dysfunction is caused by distortion of leukocyte hematopoiesis in bone marrow. (1st January 2019) - Ito, Satoyasu; Ohno, Yoshiya; Tanaka, Toshiyuki; Kobuchi, Shuhei; Ayajiki, Kazuhide; Manabe, Eri; Masuyama, Tohru; Jun-Ichi, Sakamoto; Tsujino, Takeshi
Abstract: Objective: We investigate the mechanism of neutrophil/lymphocyte ratio (NLR) elevation, a useful prognostic marker in patients with cardiovascular diseases (CVDs). Methods: In this clinical study, we retrospectively searched for factors associated with NLR elevation in cardiovascular outpatients. In animal experiments using mice with adenine-induced nephropathy, we further examined the hematopoietic process in bone marrow and explored the mechanism of NLR elevation. Result: In patients with CVDs or their risk factors, multiple regression analysis revealed that decrease in estimated glemerular filtration rate and increase in white blood cell count were significantly associated with increase in NLR. In mice with adenine-induced nephropathy, NLR and serum indoxyl sulfate (IS) levels were increased. Fluorescence-activated cell sorting revealed the increase in the number of myeloid progenitors and decrease in the number of common lymphoid progenitors, suggesting biased granulocyte side in the hematopoietic process in bone marrow. Treatment with oral charcoal adsorbent AST-120 decreased serum concentration of IS and normalized NLR and bone marrow abnormalities in mice with adenine-induced nephropathy. Conclusion: Renal function was a strong determinant of NLR in cardiovascular outpatients. NLR elevation due to renal impairment is caused by distortion of the hematopoietic process in bone marrow. IS plays a significant role in these processes.